Investigation of 29 Antimicrobial Compounds in Soil Using Newly Developed UHPLC-MS/MS Method - Gbylik-Sikorska, Małgorzata; Gajda, Anna; Felipe-Sotelo, Monica; Caniça, Manuela; Cabal-Rosel, Adriana; Tenson, Tanel; Kořínková, Marta; Arbo, Krõõt; Kisand, Veljo; Rab, Gerhard; Brandtner, Martin (Molecules (Basel, Switzerland), 2023)
While the prudent and reasonable use of veterinary antimicrobial agents in food-producing animals is necessary, researchers over the decades have shown that these antimicrobial agents can spread into the environment through livestock manure and wastewater. The analysis of the occurrence of antimicrobial compounds in soil samples is of a great importance to determine potential impacts on human and animal health and the environment. In this study, an affordable, rugged and simple analytical method has been developed for the determination of twenty-nine antimicrobial compounds from five different classes (tetracyclines, fluoro(quinolones), macrolides, sulfonamides and diaminopirimidines). Liquid-liquid extraction (LLE) with extract filtration combined with ultra-high performance liquid chromatography tandem mass spectrometry (UHPLC-MS/MS) was the best strategy for the simultaneous determination of all analytes. The developed method was validated according to the Commission Implementing Regulation (EU) 2021/808. The limit of detections (LODs) ranged from 0.5 to 2.0 µg/kg, while the limit of quantitation (LOQ) was established at 1.0 to 20.0 µg/kg. The developed method was successfully applied for the determination of antimicrobial residues in one hundred and eighteen soil samples obtained from four European countries (Austria, Czech Republic, Estonia and Portugal). Doxycycline in the concentration levels of 9.07 µg/kg-20.6 µg/kg was detected in eight of the analysed samples. Samples were collected from areas where natural fertilizers (swine or cow manure) were applied. Our method can be efficiently used to monitor anti-microbial compounds in soil samples.
Keywords: Cattle; Animals; skot; Solid Phase Extraction; Female; ženské pohlaví; Tandem Mass Spectrometry; vysokoúčinná kapalinová chromatografie; lidé; antiinfekční látky; Anti-Infective Agents; Anti-Bacterial Agents; prasata; antimicrobial agents; hnůj; Chromatography, High Pressure Liquid; Manure; tandemová hmotnostní spektrometrie; Swine; extrakce na pevné fázi; UHPLC-MS/MS; zvířata; Soil; půda; environment; antibakteriální látky; soil; Humans